2015
DOI: 10.1093/eurpub/ckv127
|View full text |Cite
|
Sign up to set email alerts
|

Medical school fails to improve Mediterranean diet adherence among medical students

Abstract: More than 70% of our medical students know very little about healthy eating and the MeDi. However, this knowledge is essential in their future profession both to support therapeutic decision-making and effective preventive actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 37 publications
6
32
0
Order By: Relevance
“…The results of this study agreed with those of other Spanish authors [5,15,71,72], who have demonstrated that about 50% of Spanish children and adolescents in other areas of Spain present good MedDiet adherence. The fact that girls have better adherence to the MedDiet than boys in this study is a reasonable finding because beginning in childhood, women are more preoccupied with body weight, which is more likely to affect their nutritional habits [73]. It was observed that when calcium intake was adequate, boys showed a slightly better adherence to the MedDiet than girls, similar to a Greek study [4].…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study agreed with those of other Spanish authors [5,15,71,72], who have demonstrated that about 50% of Spanish children and adolescents in other areas of Spain present good MedDiet adherence. The fact that girls have better adherence to the MedDiet than boys in this study is a reasonable finding because beginning in childhood, women are more preoccupied with body weight, which is more likely to affect their nutritional habits [73]. It was observed that when calcium intake was adequate, boys showed a slightly better adherence to the MedDiet than girls, similar to a Greek study [4].…”
Section: Discussionsupporting
confidence: 77%
“…Thus, medical students present suboptimal application of their academic knowledge about healthy diets in their own lives . Another cross‐sectional study with 1038 students using the KIDMED questionnaire investigated whether attending medical school may change students' MD adherence . Notably, 20.8% of the participants was categorized as having “poor” MD adherence, 56.5% as “average,” and just 22.7% as “good.” Hence, medical school attendance does not guarantee nutritional knowledge attainment.…”
Section: Adherence In Relation To Students' Study Fieldsmentioning
confidence: 99%
“…It was also found that gender was significantly associated with the adherence score, with females being 48% more likely to have a “good” KIDMED score than males, whereas medical school year was not associated with the outcomes. However, knowledge regarding nutrition was considered to be important for their future profession both to support therapeutic decision making and effective preventive actions …”
Section: Adherence In Relation To Students' Study Fieldsmentioning
confidence: 99%
“…While the investigation food HES (Health examination survey), conducted on 1,968 men and 2,062 women in 2008-2012, aged 40-59 years, resident in all Italian regions the legumes consumption both for men and women was 22 g/day [10]. A cross-sectional study on 1065 medical students shows that only 35% eat legumes more than once a week [11].Therefore the aims of the study were to investigate the legumes consumption among young and adults resident in Sicily (south Italy) and the predictive factors. …”
mentioning
confidence: 99%